Levels of active learning in programming skill acquisition: From lecture to active learning rooms - Seeling, Patrick; Eickholt, Jesse (2017 IEEE Frontiers in Education Conference (FIE), 2017)
In this paper, we perform a high-level comparison between different modifications of an entry-level programming course in computer science. The course iterations feature an online tutoring component paired with (i) textbook/traditional lecture/lab, as well as (ii) active learning in a specially designed active learning room, and (iii) active learning in a computer laboratory, both featuring an online textbook. We find that shifting the course format to active learning alone does not necessarily improve learner performance across all commonly graded course activities and might even result in lower performances in certain categories. Simply replacing traditional classroom settings with a laboratory in which to perform hands-on exercises might not be sufficient, as performance overall declined. Interestingly, we do not notice a very pronounced impact of lower performance and increased failing rates on student attitudes, as measured by student opinion scores.